Large biloma as the initial presentation of gallbladder perforation: a case report and literature review - Limani, Nimetula; Misimi, Shqipe; Nikolovski, Andrej (Oxford University Press (OUP), 2023)
Biloma is an encapsulated intra or extra-hepatic collection of bile after biliary tree trauma. Post-procedural and traumatic biliary damage are the most common etiologic causes. Gallbladder perforation due to acute cholecystitis rarely presents with biloma occurrence. We present a case of large extrahepatic biloma formation as a consequence of a perforated gallbladder.
Keywords: biloma; gallbladder perforation; acute cholecystitis